The application of instantaneous reactive power calculation methods to a real power system - (:unkn) unknown (SILA SCIENCE, 2012)
Many calculation methods have been developed to calculate the reactive power used in energy transmission lines. In this study; preferred instantaneous power calculation techniques such as instantaneous orthogonal currents, phase shifting, Peng theory and p-q power theory have been examined, these methods have been applied to the Isiklar load 2 connected to the Yatagan and Kemerkoy thermal plants via a 380 kV energy transmission line and the results have been analyzed. When the simulation results obtained from the analysis are examined; it has been determined that even though the instantaneous reactive power calculation methods used for energy transmission lines with three phase, balanced, periodical voltage and current have some differences, the instantaneous reactive power values obtained are quite close. In the study, it has been observed that the numerical calculations made by using methods to calculate the reactive power applied to a real transmission system are in accordance with simulation results.
Keywords: Instantaneous Reactive power; Active power; Reactive current; Active current; ENERGY MEASUREMENT; TURKEY; GENERATION; INTERVAL